Time-resolved three-dimensional contrast-enhanced magnetic resonance angiography in patients with chronic expanding and stable aortic dissections - Trojan, Michael; Rengier, Fabian; Kotelis, Drosos; Müller-Eschner, Matthias; Böckler, Dittmar; Kauczor, Hans-Ulrich; Tengg-Kobligk, Hendrik von (Contrast media & molecular imaging, 2017)
Objective. To prospectively evaluate our hypothesis that three-dimensional time-resolved contrast-enhanced magnetic resonance angiography (TR-MRA) is able to detect hemodynamic alterations in patients with chronic expanding aortic dissection compared to stable aortic dissections. Materials and Methods. 20 patients with chronic or residual aortic dissection in the descending aorta and patent false lumen underwent TR-MRA of the aorta at 1.5 T and repeated follow-up imaging (mean follow-up 5.4 years). 7 patients showed chronic aortic expansion and 13 patients had stable aortic diameters. Regions of interest were placed in the nondissected ascending aorta and the false lumen of the descending aorta at the level of the diaphragm (FL-diaphragm level) resulting in respective time-intensity curves. Results. For the FL-diaphragm level, time-to-peak intensity and full width at half maximum were significantly shorter in the expansion group compared to the stable group ( and ), and upward and downward slopes of time-intensity curves were significantly steeper ( and ). The delay of peak intensity in the FL-diaphragm level compared to the nondissected ascending aorta was significantly shorter in the expansion group compared to the stable group (). Conclusions. 3D TR-MRA detects significant alterations of hemodynamics within the patent false lumen of chronic expanding aortic dissections compared to stable aortic dissections.
Gesehen am 06.04.2018